Platelet Indices among Women with Pre-eclampsia attending at a Tertiary Care Hospital – A Case Control Study (Medicine Today, 2025)
Introduction: Pre-eclampsia (PE) is a pregnancy-specific hypertensive disorder characterized by endothelial dysfunction, increased systemic vascular resistance, platelet activation, and coagulation abnormalities. These changes can lead to serious complications for both mother and fetus. Platelets play a key role in vascular repair and primary hemostasis, and platelet indices—including plateletcrit (PCT), mean platelet volume (MPV), platelet distribution width (PDW), and platelet-large cell ratio (P-LCR)—reflect changes in platelet morphology and activity. Alterations in these indices have been increasingly studied as potential early markers of pre-eclampsia. Typically, platelet count decreases while MPV and PDW increase, with more pronounced changes in PE than in normotensive pregnancies. These variations can appear 2–8 weeks before the clinical onset of PE. Aim: To compare platelet indices among women with pre-eclampsia and normotensive pregnant women to evaluate their potential as early indicators for the diagnosis of pre-eclampsia. Materials and Methods: This case-control study was conducted over 12 months (June 2023 to May 2024) in the Department of Gynecology & Obstetrics at the Institute of Child and Mother Health, following ethical approval. A total of 62 pregnant women were enrolled, including 31 women with pre-eclampsia (Group A) and 31 normotensive pregnant women (Group B) as controls. After informed consent, clinical data and laboratory values were collected using structured case-record forms and analyzed with SPSS version 26. Results: Most participants were aged 21–30 years (67.7% in cases vs. 58.1% in controls, p=0.632). Systolic and diastolic pressures were significantly higher in cases. Platelet indices showed significant differences: MPV (10.58 ± 1.48 vs. 8.42 ± 1.09 fl), PDW (12.84 ± 1.53 vs. 11.19 ± 1.38 fl), P-LCR (25.97 ± 4.00% vs. 22.19 ± 2.89%), and PCT (0.2485 ± 0.0360% vs. 0.2175 ± 0.0279%) were all elevated in pre-eclamptic women (p